ANALISIS KARAKTER TOKOH DALAM NOVEL SEHIDUP SESURGA KARYA ASMA NADIA - Sarmila, Sisi; Martono, Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to find out about the exemplary character in the novel Live in Heaven by Asma Nadia. The research method used is descriptive in the form of qualitative research. The source of the data used in this study is a document in the form of a novel, namely the novel Live in Heaven by Asma Nadia and the data is the exemplary value of the character which is reflected in all the characters in the form of words, phrases, sentences related in the novel Live in Heaven by Asma Nadia. The results of this study indicate that exemplary has nine values that serve as pillars of character as follows: 1). Love of God and All of Him, 2). Independence and Responsibility, 3). Honesty/Trust, Wise, 4). Respect and Courtesy, 5). Philanthropist, likes to help, and Mutual cooperation, 6). Confident, Creative, and Hardworking, 7). Leadership and Justice, 8). Kind and Humble, 9). Tolerance, Peace and Unity. The results of this study are referred to as the implementation plan for learning Indonesian in the 2013 curriculum at the XI high school level.